Does the Phillip Curve Exist? An Econometrics Analysis Report - Wilson, Jonela (IJRDO- Journal of Educational Research, 2021)
The Phillips’ Curve is a theory that states inflation and unemployment have a stable and inverse relationship. Many scholars I have tested this theory and have found it to be true. In order to test the findings of previous scholars and to prove that this theory exists, the paper provided a set by set practical analysis. This was done by the systematic framing of traditional methodology of Econometrics to evaluate the concept of the Phillip’s Curve. The eight (8) steps of : 1. Statement of theory or hypothesis, 2. Specification of the mathematical model of the theory, 3. Specification of the statistical, or econometric, model, 4. Obtaining the data, 5. Estimation of the parameters of the econometric model, 6. Hypothesis Testing , 7. Forecasting or prediction and 8. Using the model for control or policy purposes helped in concluding that the existence of the Phillips’ Curve.